GENETIC VARIATION IN PHYSIOLOGICAL RESPONSES AND ADAPTATION OF DIFFERENT BREED OF DUCKS TO TROPICAL HEAT STRESS - Abdu, I.; Mujitaba, M.A.; Yahaya, B.; Shuaibu, A.; Jafar, A. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The Study was conducted at the Poultry unit of the Teaching and Research Farm of Abubakar Tafawa Balewa University, Bauchi to determine the genetic variation on physiological and adaptation responses of three duck breeds. Data on physiological parameters: pulse rate (PR), respiratory rate (RR) and rectal temperature (RT) of twenty-five (25) matured ducks, comprising ten (five males and five females) each of Muscovy and Khaki Campbell and five (two males and three females) of White Pekin ducks were obtained and subjected to analysis of variance. Breed had significant (P<0.001) effects on all the physiological parameters. White Pekin had the highest PR (186.80±0.39 beat/minute), RR (31.43±0.19 breath/minutes) and RT (41.79±0.10°C), while the least were recorded among Muscovy ducks (145.98±0.48 beat/minute, 23.61±0.16 beat/minute, and 41.34±0.71°C, respectively). Similarly, all physiological parameters recorded were significantly affected (P<0.001) by the period of the day. The highest responses were observed in the afternoon. Significant (P<0.001) effects of sex on PR and RR were detected. Females exhibited higher responses than males. However, a non-significant influence of sex on RT was observed. A significant (P<0.001) breed x period of the day and breed x sex interactions existed on all the parameters. The research has shown that Muscovy ducks were more tolerant to heat stress than Khaki Campbell and White Pekin. Adequate measures should be employed to alleviate heat stress on ducks during the hot season. This study could serve as a baseline for the genetic improvement of ducks in the tropics